VD_FINDINFO HC / 2015 / 990 vom 18. November 2015 - VD Tribunal cantonal (2015)
PROTECTION DE L'UNION CONJUGALE, TRANSACTION JUDICIAIRE, ASSISTANCE JUDICIAIRE | 109 CPC (CH), 122 CPC (CH), 241 CPC (CH)